Increasing the Interest of Grade XI.10 Students in Learning Civic Education Through Genially Media at SMA Negeri 3 Palembang - Jesan, Sesillia Mutiara; Kurnisar, Kurnisar; Mutiara, Tyas Masito (Departement of PAI, Universitas Majalengka, 2025)
This research aims to explain efforts to apply genially learning media as a solution to increase students' interest in learning in class XI.10 at SMA Negeri 3 Palembang. The research method used is classroom action research which is carried out with 3 learning cycles consisting of Pre-action or Pre-cycle, Post-action (Cycle 1), and Post-action (Cycle 2). The subjects of this research were 30 students in class XI.10 of SMA Negeri 3 Palembang. The indicators of interest in learning used are feelings of joy, student interest, student involvement, being diligent in studying, and being diligent and disciplined in learning. The results of this research show that Genially learning media can increase students' interest in learning. This can be seen from the results of the interest in learning questionnaire with success criteria of 76%-100% being declared high, 56-75.9% being declared medium, 0%-55.9% being declared low. From the results of the pre-action activities, the average obtained was 48.83% in the low category and continued in the 1st cycle of post-action activities, the percentage was 68.9% in the medium category and continued to increase in the 2nd cycle of post-action activities with a percentage of 80. 2% in the high category. So it can be concluded that Genially learning media can increase students' interest in learning in class XI.10 at SMA Negeri 3 Palembang.